Rural areas endangered with depopulation as problem areas – the example of Poland - Wojewódzka-Wiewiórska, Agnieszka (Obszary wiejskie zagrożone depopulacją jako obszary problemowe – przykład Polski, 2021)
The article deals with the problem of population decline in Poland in local terms. The aim of the study was to present the changes in the population number in rural areas in the period 1998-2018 and to indicate the negative socio-economic consequences that occur in rural areas affected by depopulation, which means that they have the characteristics of problem areas. The data from Statistics Poland and the results of own research carried out in a rural commune in Podlaskie voivodeship were used. In statistical data analysis, the multiple linear regression method was applied. It was found that 41.5% of rural communes were characterized by a population decline of over 5%, while in 7.7% of communes the decline in the population was greater than 15%. The own author’s research revealed that the problem of population decline is accompanied by other negative phenomena, such as a distorted structure of the population by age, gender, limited access to services and infrastructure development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 4, s. 158-170
Keywords: rural areas; problem areas; commune; local development; depopulation; obszary wiejskie; obszary problemowe; gmina; rozwój lokalny; depopulacja